Tourist Attractions, Motivation, and Satisfaction as Determinants of Revisit Intention to Natural Destinations: A Case Study in Batur Geopark, Bali - Ni Putu Ratna Sari; I Wayan Sukma Winarya Prabawa; Anak Agung Gde Raka Dalem; Putu Ratih Pertiwi; I Putu Andre Adi Putra Pratama (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2026)
Aims of this study was to examine the influence of tourist attractions, motivation, and satisfaction on revisit intention to Batur Geopark, Bali. This study also investigated the mediating role of motivation and satisfaction in the relationship between tourist attractions and revisit intention. The background of this research was based on the phenomenon that tourist visits were often driven by the desire to relax, escape daily routines, and enjoy nature-based experiences. When these desires were  fulfilled, satisfaction emerged and lead to memorable experiences. A quantitative method with Structural Equation Modeling–Partial Least Squares (SEM-PLS) was employed, using accidental sampling with 200 respondents. The findings indicated that the more diverse and appealing the available tourist attractions such as glamping, mountain trekking for sunrise views, jeep tours, ATV rides, and the Geopark Museum the higher the motivation and satisfaction levels of tourists. Furthermore, motivation and satisfaction partially mediated the effect of tourist attractions on revisit intention. This confirms that revisit intention to Batur Geopark was strongly influenced by both internal motivations and the satisfaction derived from the overall tourist experience. These findings highlighted the importance of continuously enhancing the quality and variety of attractions in alignment with tourists’ experiential needs.